Number of directional changes alters the physiological, perceptual, and neuromuscular responses of netball players during intermittent shuttle running - Ashton, R. E. M.; Twist, C. (The Journal of Strength and Conditioning Research, 2015)
This study investigated whether an increased number of changes in direction altered the metabolic, cardiovascular, perceptual, and neuromuscular responses to intermittent shuttle running (ISR). Using a randomized crossover design, 10 female netball players completed 30 minutes of ISR over a 10-m (ISR10) and 20-m (ISR20) linear course. Measures of expired air, heart rate (HR), rating of perceived exertion, blood lactate concentration ([BLa]), and peak torque of knee extensors and flexors were measured. Differences (%change ± 90% CL) in VO2 (1.5 ± 5.6%) was unclear between conditions, whereas HR was possibly higher (1.5 ± 2.5%) and [BLa] very likely lower in ISR20 compared with ISR10 (-32.7 ± 9.9%). Rating of perceived exertion was likely lower in the ISR20 compared with the ISR10 condition at 15 (-5.0 ± 5.0%) and most likely lower at 30 minutes (-9.4 ± 2.0%). Sprint times over 20 m were likely slower during ISR20 at mid (3.9 ± 3.2%) but unclear after (2.1 ± 5.4%). Changes in muscle function were not different between ISR10 and ISR20 conditions for knee extension (-0.2 ± 0.9%) but were likely different for knee flexion (-5.7 ± 4.9%). More directional changes during shuttle running increase the physiological and perceptual load on female athletes, which also cause a greater reduction in knee extensor torque. These findings have implications for the effective conditioning and injury prevention of female team sport athletes.